Nucleolar organizer regions in somatic chromosomes of some species of birds - Rocha, Guaracy Tadeu [UNESP]; de Lucca, Edmundo José [UNESP] (Firenze University Press, 1988)
Nucleolar organizer regions (NORs) were investigated in 8 species of birds. The species Gallus domesticus, Columba livia, Columbina talpacoti and Molothrus bonariensis have only 1 NOR-bearing microchromosome pair. In the species Guira guira and Pitangus sulphuratus, the NOR is located in the satellite region of the 9th chromosome pair. Speotyto cunicularia showed NORs in variable numbers of microchromosome, and Mimus satuminus, in addition to weak staining in variable numbers of microchromosomes, exhibited positive NOR-staining on the short arm of the 3rd chromosome pair. The presence of NORs in macrochromosomes and the occurrence of asymmetry in NOR staining are discussed. © 1988 by the Japan Society for Bioscience, Biotechnology, and Agrochemistry.